Utilización de dos Enzimas (amilasa, fitasa) en la Dieta de Pollos de Engorde - Chicaiza Quile, Cesar Fabián (2018)
This project was carried out in Tungurahua Province, Ambato Canton Pishilata Parish, American Park Neighborhood, where the general objective was to evaluate the use of two types of enzymes (amylase, phytase) in the diet of broilers due to the input costs and deficiency of nutrients in the food of chickens, the researchers proceeded to carry out this research for which eighty-four broilers were used at one day of age, at fourteen days were distributed in three treatments and four repetitions in wooden boxes with an experimental unit of seven chickens; they were distributed under a completely randomized design (DCA), T0 Control was supplied with a food diet without the addition of enzymes, T1 one was provided with a food diet added amylase 14 grams per each 45 kg of balanced and T2 was fed a dietary supplement added Phytase 14 grams per 45 kilograms of balanced. The experimental project was divided into two phases: growth (0-21 days) and fattening (28-49 days). The evaluation method was to use variables with experimental results processed in Infostat and Excel, which were subjected to an analysis of variance (ADEVA) and Fisher's test for the separation of means with a significance of P <0.05, which were initial weight that was homogeneous where the average was for the T0 (control) 41.23 g, T1 (Amylase) 41.18 g, T2 (Phytase) 41.03 g, the final weight determined that the T2 (Phytase) reached an average weight of 2944.78 g, followed by T1 (Amylase) with 2844.38 g, the lowest weight was T0 (Control) with 2707.30 g.